"It kind of fosters a culture of interdependence": A participatory appraisal study exploring participants' experiences of the democratic processes of a peer‐led organisation. (5th March 2019) - Budge, Gemma; Mitchell, Annie; Rampling, Terry; Down, Patrick; ,
Abstract: Peer‐led mental health organisations operate through participatory democracy, enabling participants to take an active role in decision making about the running of these organisations. U.K. national policy recommends increased involvement of people accessing statutory mental health services in service development, for example, through co‐production. This study employed a participatory research method to explore participants' perspectives of the democratic processes of a U.K.‐based peer‐led mental health organisation, The Bridge Collective, and the influence of these processes on participant wellbeing. A range of data collection methods were used to gather the perspectives of 16 participants. Participatory thematic analysis identified how the organisations' democratic processes both nurtured and challenged participants' wellbeing. Three main themes captured the influences of the democratic processes on participant wellbeing: (a) negotiating relationships, (b) feeling the responsibility of involvement, and (c) sharing power. The findings identify the value of democratic processes in enabling meaningful social support and empowerment, and also identify the challenges of inclusion and workload management in participatory democracy. These insights may inform the development of co‐production methods and enable The Bridge Collective and other peer‐led organisations to further develop their processes.